STUDI DESKRIPTIF PERBEDAAN MOTIVASI BERWISATA KE SEOUL, KOREA - Natasha Naftali; Erna Andajani; Siti Rahayu (Perpustakaan Universitas Surabaya, 2018)
This study airms to identify motivation Indonesian tourist to Seoul, South Korea use the theory push and pull motivation as a framework conceptual anf know the difference motivation go to Seoul, South Korea on the basis of gender, age, education, and income. This processing was done in use spss 22 for windows. Technique the sample use is non probability sampling the sample of the used in this research was 200 respondents. Data processed use mean, standart deviation, the independent sample t-tes and one way anova. This statement said 3 push dimensions which are (1) novelty and knowledge seeking (2) egoenhancement (3) rest and relaxation, and 3 pull dimension (1) environment and safety (2) cultural and historical attraction (3) tourism facilities. That is devided into 36 statement that has beeb done the adjustment of a previous studies of the six demensions push and pull seoul, South Korea dimensions rest and relaxation described the best of the total an average of 4,36 and standart deviation 0,730.